2002
DOI: 10.1002/eat.10087
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of ovarian and uterine maturity in adolescents with anorexia nervosa

Abstract: Previous target weights have been too low to ensure reproductive maturity. The resulting hypoestrogenic state increases the risk of future osteoporosis. Pelvic ultrasound is the safest and most reliable method for determining ovarian and uterine maturity in adolescent girls with anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…With increasing gonadal recovery, a dominant follicle may be seen, and menstruation has been observed within a month in 50%. 43 Only 41% of adolescents recovering from AN have mature ultrasound appearance of the ovaries and uterus at a weight to height ratio of 95%, 45 illustrating the delay between weight recovery and complete recovery of gonadal function, and the importance of nutritional factors. 7 A promising new tool for monitoring recovery in AN may be inhibin B, a marker of ovarian follicular development.…”
Section: Hormone Adaptation In Anmentioning
confidence: 99%
“…With increasing gonadal recovery, a dominant follicle may be seen, and menstruation has been observed within a month in 50%. 43 Only 41% of adolescents recovering from AN have mature ultrasound appearance of the ovaries and uterus at a weight to height ratio of 95%, 45 illustrating the delay between weight recovery and complete recovery of gonadal function, and the importance of nutritional factors. 7 A promising new tool for monitoring recovery in AN may be inhibin B, a marker of ovarian follicular development.…”
Section: Hormone Adaptation In Anmentioning
confidence: 99%
“…Several authors have described the use of ultrasonographic appearances of the uterus and ovaries as a more objective, accurate, reliable and valid means of tracking progress of patients with AN (Treasure, Gordon, Wheeler & Russell, 1985;Lai, de Bruyn, Lask, Bryant-Waugh & Hankins, 1994;Key et al, 2002;Mason, Key, Allan & Lask, 2007). Their findings have suggested that the WfH ratios needed for reproductive maturity are higher than those that are generally set as targets.…”
Section: Introductionmentioning
confidence: 95%
“…Their findings have suggested that the WfH ratios needed for reproductive maturity are higher than those that are generally set as targets. For example Frisch and McArthur (1974) and Golden et al (2008) have suggested a target range of between 87 and 92% WfH whereas Lai et al (1994) and Key et al (2002), using pelvic ultrasound have found that the majority of such patients do not reach reproductive maturity with a WfH ratio below 96.5%.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations